2021
DOI: 10.1111/icad.12446
|View full text |Cite
|
Sign up to set email alerts
|

Spectral optimization of beacon lights for the protection of night‐swarming mayflies

Abstract: 1. Negative ecological effects of artificial night-time illumination on wildlife are becoming more and more widely investigated. Flight-to-light behaviour of insects is a well-known phenomenon, which becomes really conspicuous when numerous individuals are simultaneously attracted to light. Mass mortality of night-swarming mayflies at lamp-lit urbanized areas, particularly at bridges, is a well-known phenomenon.2. White beacon lights are able to keep the mayfly swarms above the water surface. Firstly, it is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In "Tatort Streetlight" data, the orders Ephemeroptera and Trichoptera constitute a significant proportion of the insects collected. The differences in numbers of individuals caught at day and night-time indicate a high vulnerability of these insect groups to road lights close to freshwater bodies, which corroborates prior studies [39,65]. Another group that might be disproportionally affected by artificial light near freshwater ecosystems contains aquatic Heteroptera [66], which were also found significantly more often in the night-time samples.…”
Section: Insect Monitoringsupporting
confidence: 85%
“…In "Tatort Streetlight" data, the orders Ephemeroptera and Trichoptera constitute a significant proportion of the insects collected. The differences in numbers of individuals caught at day and night-time indicate a high vulnerability of these insect groups to road lights close to freshwater bodies, which corroborates prior studies [39,65]. Another group that might be disproportionally affected by artificial light near freshwater ecosystems contains aquatic Heteroptera [66], which were also found significantly more often in the night-time samples.…”
Section: Insect Monitoringsupporting
confidence: 85%
“…Several detailed plans have been drawn up to mitigate the impact of ALAN especially in protected areas (Jägerbrand and Bouroussis 2021). For example, in Hungary, researchers have successfully reduced attraction of many species of the Ephemeroptera to light by optimising the spectrum of beacon lights on a bridge such that the adults do not show a mass phototactic response (Mészáros et al, 2021). Since adult Ephemeroptera live only for a few hours, and spend their development stages in water, the judicious adoption of such mayfly-protecting lights near water bodies is a practical mitigation measure.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…In a recent study, when our primary aim was to optimize a phototaxis-based mayfly protecting system [12] (electronic supplementary material, movie S4), we revealed that the attraction of E. virgo and another twilight-swarming mayfly ( Caenis macrura Stephens, 1836) to light is the highest for UV and blue light and decreases with increasing wavelength [13]. Similar results were reported for other, non-identified twilight-swarming mayfly species [14].…”
Section: Introductionmentioning
confidence: 99%